Effects of remote haemodynamic‐guided heart failure management in patients with different subtypes of pulmonary hypertension: insights from the MEMS‐HF study. (3rd November 2022) - Assmus, Birgit; Angermann, Christiane E.; Alkhlout, Basil; Asselbergs, Folkert W.; Schnupp, Steffen; Brugts, Jasper J.; Nordbeck, Peter; Zhou, Qian; Brett, Marie‐Elena; Ginn, Greg; Adamson, Philip B.; Böhm, Michael; et al.
Abstract : Aim: The CardioMEMS European Monitoring Study for Heart Failure (MEMS‐HF) investigated safety and efficacy of pulmonary artery pressure (PAP)‐guided remote patient management (RPM) in New York Heart Association (NYHA) class III outpatients with at least one heart failure hospitalization (HFH) during the previous 12 months. This pre‐specified subgroup analysis investigated whether RPM effects depended on presence and subtype of pulmonary hypertension (PH). Methods and results: In 106/234 MEMS‐HF participants, Swan–Ganz catheter tracings obtained during sensor implant were available for off‐line manual analysis jointly performed by two experts. Patients were classified into subgroups according to current PH definitions. Isolated post‐capillary PH (IpcPH) and combined post‐ and pre‐capillary PH (CpcPH) were present in 38 and 36 patients, respectively, whereas 31 patients had no PH. Clinical characteristics were comparable between subgroups, but among patients with PH pulmonary vascular resistance was higher ( p  = 0.029) and pulmonary artery compliance lower ( p  = 0.003) in patients with CpcPH. During 12 months of PAP‐guided RPM, all PAPs declined in IpcPH and CpcPH subgroups (all p  < 0.05), whereas only mean and diastolic PAP decreased in patients without PH (both p  < 0.05). Improvements in post‐ versus pre‐implant HFH rates were similar in CpcPH (0.639 events/patient‐year; hazard ratio [HR] 0.37) and IpcPH (0.72 events/patient‐year; HR 0.45) patients. Participants without PH benefited most (0.26 events/patient‐year; HR 0.17, p  = 0.04 vs. IpcPH/CpcPH patients). Quality of life and NYHA class improved significantly in all subgroups. Conclusions: Outpatients with NYHA class III symptoms with at least one HFH during 1 year pre‐implant benefitted significantly from PAP‐guided RPM during post‐implant follow‐up irrespective of presence or subtype of PH at baseline.